REPORT ON THE ROUND-TABLE MEETING: "REGISTERS IN CARDIOLOGY: THE BASIC RULES OF MANAGEMENT, MODERN EXPERIENCE AND THE RESULTS OF THEIR CREATION IN THE VARIOUS REGIONS OF THE RUSSIAN FEDERATION" - S. Yu. Martsevich; M. M. Loukianov; N. P. Kutishenko (Рациональная фармакотерапия в кардиологии)
The results of the round-table meeting "Registers in cardiology: the basic rules of management, modern experience and the results of their creation in the various regions of the Russian Federation" are presented. Experts from different cities of Russia, who were involved in carrying out the registers of various cardiovascular diseases (CVD) were among participants of the meeting. The importance of modern registers to assess the real state of prevention, diagnosis and treatment in the different institutions providing practical health care is stressed. The need in rapid implementation of register’s conclusions into practice in order to improve health care quality and to increase efficiency of CVD and their complications prevention is indicated.